Effects of Incorporation of Jackfruit Rind Powder on Chemical and Functional Properties of Bread - Reza Felli; Tajul Aris Yang; Wan Nadiah Wan Abdullah; Wahidu Zzaman (Tropical Life Sciences Research, 2018)
Nowadays, there is a rising interest towards consuming health beneficial food products. Bread–as one of the most popular food products–could be improved to ‘healthy bread’ by addition of ingredients high in protein, dietary fiber and low in calorie. Incorporating Jackfruit rind powder (JRP) as a by-product rich in dietary fiber in bread, could not only provide health beneficial bread products, but also lead to develop an environmental friendly technology by solving the problem of waste disposal of residues. In this study, addition of jackfruit rind powder (JRP) as a high dietary fiber and functional ingredient in bread was examined. The results showed that incorporation of JRP in bread improved functional properties of flour such as Oil Holding Capacity (OHC), Water Holding Capacity (WHC) and pasting properties. Addition of 5%, 10% and 15% of JRP in wheat flour caused significantly (p < 0.05) higher insoluble, soluble and total dietary fiber in flour and bread products. Results from proximate composition indicated that all breads substituted with JRP, contained significantly (p < 0.05) higher fiber, moisture and fat. Obtained results confirmed that the JRP has great potential in development of functional foods especially functional bread products.